2008
DOI: 10.1088/1367-2630/10/5/055007
|View full text |Cite
|
Sign up to set email alerts
|

An extensive comparison of anisotropies in MBE grown (Ga,Mn)As material

Abstract: This paper reports on a detailed magnetotransport investigation of the magnetic anisotropies of (Ga,Mn)As layers produced by various sources worldwide. Using anisotropy fingerprints to identify contributions of the various higher order anisotropy terms, we show that the presence of both a [100] and a [110] uniaxial anisotropy in addition to the primary ([100] + [010]) anisotropy is common to all medium doped (Ga,Mn)As layers typically used in transport measurement, with the amplitude of these uniaxial terms b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 16 publications
1
28
0
Order By: Relevance
“…͑A weak uniaxial component along the main crystal axes ͓͑100͔/͓010͔͒ has also been detected. 45,46 ͒ The theoretical model used so far to describe the easy-axis reorientation between the in-plane and out-of-plane alignment, assuming the growth strain, can account only for the cubic in-plane anisotropy component. In this case we find two easy axes perpendicular to each other either along the main crystal axes or along the diagonals, depending on the Mn concentration and hole density, as shown in Fig.…”
Section: B In-plane Anisotropy: Competition Of Cubic and Uniaxial Comentioning
confidence: 99%
“…͑A weak uniaxial component along the main crystal axes ͓͑100͔/͓010͔͒ has also been detected. 45,46 ͒ The theoretical model used so far to describe the easy-axis reorientation between the in-plane and out-of-plane alignment, assuming the growth strain, can account only for the cubic in-plane anisotropy component. In this case we find two easy axes perpendicular to each other either along the main crystal axes or along the diagonals, depending on the Mn concentration and hole density, as shown in Fig.…”
Section: B In-plane Anisotropy: Competition Of Cubic and Uniaxial Comentioning
confidence: 99%
“…␦ / 2 is determined by the angle difference between the corners of the rectangle defined by the first switching fields ͑green circles͒ close to the ͓100͔ and ͓010͔ directions. 18 These corner points are also the directions where first and second switching fields coincide. We obtain ␦ / 2=͑15Ϯ 2͒°, indicating that the global easy axes are located ͑60Ϯ 2͒°from the ͓110͔ direction and ͑30Ϯ 2͒°from the ͓110͔ direction, respectively.…”
mentioning
confidence: 91%
“…It has been demonstrated that a number of pertinent properties of this material can be explained by the p-d Zener model. [3][4][5][6] Magnetic anisotropy of strained ͑Ga,Mn͒As layers can be calculated within this theory and many experimental studies [7][8][9][10][11][12][13][14][15] were devoted to verify its predictions. However, despite these intense studies, some important features of magnetic anisotropy in this system are at present not completely understood.…”
Section: Introductionmentioning
confidence: 99%